North Syria in the Early First Millennium B.C., with Special Reference to Ivory Carving - Winter, Irene J. (1973)
Ph.D. Dissertation; University Microfilms (Order No. 76-7357) Ann Arbor, MI © 1975. 632 p., 184 fig. Advisor: Edith Porada.